A high-performance multilevel inverter with reduced power electronic devices - Amer Chlaihawi; Adnan Sabbar; Hur Jedi (Institute of Advanced Engineering and Science, 2020)
This paper introduces a new topology of multilevel inverter, which is able to operate at high performance. This proposed circuit achieves requirements of reduced number of switches, gate-drive circuits, and high design flexibility. In most cases fifteen-level inverters need at least twelve switches. The proposed topology has only ten switches. The inverter has a quasi-sine output voltage, which is formed by level generator and polarity changer to produce the desired voltage and current waveforms. The detailed operation of the proposed inverter is explained. The theoretical analysis and design procedure are given. Simulation results are presented to confirm the analytical approach of the proposed circuit. A 15-level and 31-level multilevel inverters were designed and tested at 50 Hz.